Resistance to Gonorrhea Possibly Mediated by Bacterial Interference - Kraus, Stephen J. (1974)
Two men with no prior history of urethritis failed to develop gonorrhea after sexual exposures to women with genital gonococcal infection. Usual methods of prophylaxis, such as antibiotics or condoms, were not employed. The aerobic bacterial flora of these men's urethras consisted of several bacteria, some of which inhibited the in vitro growth of Neisseria gonorrhoeae. The hypothesis is suggested that bacterial interference may have played a role in protecting these men from gonorrhea.